PENERAPAN METODE BERMAIN PERAN DALAM MENGEMBANGKAN SIKAP SOSIAL ANAK USIA DINI DI ROUDHOTUL ATFHAL AL-ISHLAH SUKA DAMAI NATAR LAMPUNG SELATAN TAHUN PELAJARAN 2023/2024 - Ambar Wati (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This research is based on the problem of the low social skills of young children, and in general the problem of this research is "How to improve children's social skills through the application of role playing methods in Roudhotul atfhal al-ishlah like peace Natar South Lampung Academic year 2023/2024 ?” which is formulated as follows: (1) How is the role playing method applied in improving children's social skills in Roudhotul atfhal al-ishlah like peace Natar, South Lampung? The aim to be achieved is to obtain an overview of improving the social skills of early childhood in Roudhotul atfhal al-ishlah like peace Natar, South Lampung through the application of role-playing methods. The research method used is Classroom Action Research (PTK) to improve the learning process of children's social skills and speaking skills through the application of role-playing methods. PTK was carried out in two cycles, with the subject being 25 children from group B, Roudhotul atfhal al-ishlah, like peace, Natar, South Lampung. From the results of the implementation and observations made, there was quite a large increase, especially in cycle two. It is recommended for teachers that social skills and speaking skills be further developed, both in learning, implementing and evaluating learning. It is hoped that future researchers will be able to conduct research on children's social and speaking skills using other methods.